AKTIVITAS ANTIOKSIDAN EKSTRAK UMBI SUWEG (Amorphophallus paeoniifolius) DARI BERBAGAI TINGKAT POLARITAS PELARUT - Deddy Firman; Nurhaeni Nurhaeni; Ahmad Ridhay (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT Has done research about antioxidant activity of suweg tuber (Amorphophallus campamulatus) based on the level of polar solvent. This research begins with in phased maceration extraction using n-hexane, ethyl acetate dan ethanol. Next step was antioxidant activity test with tyocyanate to n-hexane extract and DPPH methods to ethanol extract, ethyl acetate and vitamin C. The result showed antioxidant activity in n-hexane extract i.e. 14,96 %, end 77,13 % BHT while in ethyl acetate, ethanol and vitamin C reached IC50 value are 458,102 ppm, 223,268 ppm dan 26,76 ppm. Keywords: Suweg tuber, type of solvent, maceration, antioxidant